Where the wildflowers grow : a novel - Harris, Terah Shelton (Sourcebooks Landmark, 2026)
"Leigh is the last of the Wildes. She knows this because she watched them all die. Grief never truly fades and even as the tragedy haunts her, Leigh carries on, because survival is in her blood. So, when the transport bus taking her to prison careens off the road, killing everyone onboard except her, she does what's in her nature. She survives. While searching for a place to hide, Leigh stumbles upon an unexpected sanctuary: a flower farm in rural Alabama tucked away from the world. What Leigh doesn't expect is the found family there who have built something from the wreckage of their own lives. Especially Jackson, the farm's owner, who sees through Leigh's defenses, offers her small moments of tenderness, encourages her to face her own tragedies. Slowly, Leigh finds peace with the hard pace and soft nature of the farm, taking comfort in the life blooming around her. Maybe she's not beyond redemption, not too broken for something good. And maybe, just maybe, Leigh starts to heal. But the past isn't so easily buried. No matter how far she runs, the truth of who she is--and the ghosts of the Wildes--follow. And when those secrets catch up to her, threatening everything she's come to love, Leigh will have to truly face what she can survive."--